Applicant characteristics associated with successful matching into otolaryngology. (21st October 2016) - Hauser, Leah J.; Gebhard, Grant M.; Blumhagen, Rachel; Carlson, Nichole E.; Cabrera‐Muffly, Cristina
Abstract : Objective: To identify resident applicant characteristics that increase the odds of matching to otolaryngology residency. Study Design: Cross‐sectional analysis. Methods: Residency applications to our institution from 2009 through 2013 were reviewed. The available data represented 81.1% of applicants to otolaryngology programs nationwide. Online public records were searched to determine whether an applicant matched to an otolaryngology residency position. Factors that were significantly associated with the odds of matching were determined using logistic regression. Results: A total of 1, 479 unique applications were analyzed. On univariate analysis, 27 demographic, academic, personal, medical school, prior training, and application‐specific factors were associated with the odds of matching into otolaryngology. On multivariate analysis, indicators of academic achievement, such as Alpha Omega Alpha Honor Medical Society (AOA) status, whether applicant received awards, and publications, were significantly associated with the odds of matching (odds ratio [OR] 2.03, 1.39, 1.66, respectively). The odds of matching increased with increasing step 1 scores ( P < 0.001). Attending a medical school ranked by the U.S. News & World Report and being a U.S. citizen born in the United States significantly increased the odds of matching (OR 1.55 and 2.04, respectively), whereas being a non‐U.S. senior medical student significantly decreased the odds of matching (OR 0.33). Conclusion: Multiple factors are associated with successfully matching into an otolaryngology residency. Although this information allows medical students to determine the strength of their application, these criteria have not been correlated with resident success. We urge selection committees to begin identifying applicant selection methods that reflect the values we want to cultivate in our future colleagues. Level of Evidence: N/A. Laryngoscope, 127:1052–1057, 2017